The “Family Health = Family Wealth” intervention: study protocol for a pilot quasi-experimental controlled trial of a multi-level, community-based family planning intervention for couples in rural Uganda - Katelyn M. Sileo; Christine Muhumuza; Samuel Sekamatte; Haruna Lule; Rhoda K. Wanyenze; Trace S. Kershaw; Susan M. Kiene (Pilot and Feasibility Studies, 2022)
Abstract Background Uganda has one of the highest fertility rates globally, but only 30% of women report using an effective method of contraception. Community-based, multi-level interventions are needed to help couples in rural Uganda overcome barriers to contraceptive use. Methods This study will pilot test the Family Health = Family Wealth intervention, a multi-level, community-based intervention employing transformative community dialogues, which use facilitated discussion to reshape community norms that influence family planning acceptance, to alter individual attitudes and the perception of community norms that discourage family planning. Community dialogues are delivered to groups of couples over 4 sessions (two gender-segregated and two gender-mixed). Sessions simultaneously address individual and interpersonal-level determinants of family planning and link couples to family planning services. At the health system level, a refresher training will be conducted with health workers in the intervention community’s health center to address gaps in contraceptive knowledge and skills as identified from a needs assessment. The intervention will be evaluated through a pilot quasi-experimental trial paired with a mixed methods process evaluation. Participants include 70 couples (N=140) randomized by community to the Family Health = Family Wealth intervention (n=35 couples) or to an attention-matched water, sanitation, and hygiene (WASH) intervention (n=35 couples). Participants include sexually active, married couples who are age 18 (or an emancipated minor) to 40 for women and age 18 (or an emancipated minor) to 50 for men, not pregnant, at least one person in the couple reports wanting to avoid pregnancy for at least a year, and not currently using a method of contraception or using a low-efficacy or ineffective method of contraception. The primary aims of the study are to (1) assess the feasibility of the intervention trial procedures, (2) the acceptability and feasibility of the intervention content and structure, and (3) explore the intervention’s preliminary effectiveness at increasing contraceptive use and affecting related outcomes among couples. Discussion Filling the unmet need for family planning has important public health implications, including reductions in pregnancy-related health risks and deaths, and infant mortality. This pilot intervention trial will gather preliminary evidence on the acceptability, feasibility, and potential effect of a novel, multi-level, community-based intervention to increase contraceptive use among couples with an unmet need for family planning in rural Uganda. We aim to use the findings of this pilot study to refine the trial procedures and intervention content for a future, larger cluster randomized controlled trial to establish the intervention’s efficacy. Trial registration ClinicalTrials.gov NCT04262882; registered on February 10, 2020.